Chlorhexidine sensitivity in staphylococci isolated from patients with central line-associated bloodstream infection. Issue 3 (November 2019) - Jun, K.I.; Choi, Y.; Kwon, K.; Shin, M.J.; Park, J.S.; Song, K-H.; Kim, E.S.; Park, K-H.; Jung, S-I.; Cheon, S.H.; Kim, Y-S.; Yoon, N-R.; et al.
Summary: Since 2011, 2% chlorhexidine in 70% isopropyl alcohol (2% chlorhexidine tincture) has been widely used in Korea. To investigate changes in chlorhexidine sensitivity of staphylococci causing central line-associated bloodstream infections, 264 blood culture isolates from adult patients treated in intensive care units of five university hospitals between 2008 and 2016 were analysed. We observed no significant changes in chlorhexidine minimum inhibitory and bactericidal concentrations, or in the prevalence of resistance-associated genes before and after introduction of 2% chlorhexidine tincture. Thus, there was no evidence of increased resistance to chlorhexidine in staphylococci causing central line-associated bloodstream infections.